Ready to go? Profiling Philippines high school teachers’ readiness for blended learning in post-COVID-19 era - Bonifacio Vergonia; Sanny Eriman Mombas (Journal of Educational Management and Instruction (JEMIN), 2022)
In post-COVID-19 era, education system around the world seems to experience a shifting from traditional in-class learning to online activities, or it can be blended style which is the combination of both modes. Hence, exploring teachers’ and learners’ readiness for the different model of learning activities is a must and becomes a worth inquiry. The present study is at the cutting edge of profiling high school teachers’ readiness for blended teaching activities in Philippines at the time of post-COVID-19 era. A survey research design was adopted by involving 107 high school teachers in the city of Tupi, South Cotabato province, Philippine. This study provided an alluded picture that Philippines high school teachers are ready to conduct a blended learning system in post-pandemic era. This conclusion was drawn from the excellent results of survey items in four dimensions for blended teaching readiness model developed by Graham et al, comprising technical literacy, planning blended activities, facilitating student-student and teacher-student interaction, and managing the blended learning environment. The results indicate that a responsive, supportive, and relevant teacher professional development programs should be developed in order to enhance teachers’ readiness for blended learning in post-COVID-19 era, as well as improving Philippines future educational system.